Determinación de la huella de carbono organizacional en el Ceasa para elaborar una propuesta de manejo en el período 2013 - 2014 - Laverde Mora, Paola Elizabeth (2014)
This thesis carries out a detailed calculation of the carbon footprint organizational of the CEASA at Technical University of Cotopaxi, with the aim of drawing up a management proposal plan to minimize the input of CO2 equivalent by the CEASA to the environment, thus reducing the consumption of resources and generation of residue as an environmental pollution. The CEASA is the Experimental and Academic Center Salache which is part of Technical University of Cotopaxi; in this Center works CAREN Academic Unit "Agricultural sciences and Natural Resources", it is located in Salache Parish, Latacunga Canton, Cotopaxi Province. The rules on which this calculation was based were: Gases Protocol gases, ISO standards 14064 part 1, 2 and 3; the method used for the calculation is the same MC3 which was developed by Rees and Wackernagel at the end of the year 2000. To perform the calculation information was obtained from all those who are part of the CEASA....